Sovereign Spreads and Contagion Risks in Asia - Unsal, Filiz; Caceres, Carlos (Washington, D.C. : International Monetary Fund, 2011)
This paper explores how much of the movements in the sovereign spreads of Asian economies over the course of the global financial crisis has reflected shifts in (i) global risk aversion; (ii) country-specific risks, directly from worsening fundamentals, and indirectly from spillovers originating in other sovereigns and the uncertainty surrounding exchange rates. Earlier in the crisis, the increase in market-implied contagion led to higher Asian sovereign bond yield spreads over swaps. But, after the crisis, Asia's sovereign spreads normalized, despite the debt crisis in the euro area, reflecting a fall in both exchange rate and spillover risks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet